(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
Throughout the eighties and nineties, one of the key places for the development of video art in the Spanish state was the Basque Country. Among the works of that time, those created by reusing images from women’s magazines stand out. Through photocopies, cutouts or even involving the body itself, the artists critically reinterpreted the promotion of the feminine aesthetic canon. The article suggests that common tactics of academic interest were used in this critique and advocates for the enhancement of the selected works, considering them key to the construction of a historiography of feminist art. To make this contribution, first of all, a framework is created around the canon of beauty from the end of the 20th century, to later analyse four creations by the artists Elena Marrodan and Estibaliz Sádaba. The analysis of the works is developed through the cross-sectional study of two elements: the aesthetics of uniformity and punk music. In this way, it is explored how the aesthetic homogenization promoted by the beauty canon was criticized, to later explain what meaning the punk music used in the works added.The abstract should be a concise statement of the subject, approach and conclusions.